Use of cryotherapy in different diseases - Jaworski, Piotr (Journal of Education, Health and Sport, 2019)
Physiotherapy section - physicotherapy successfully applies frequent cryotherapy treatments in many different diseases. The paper presents a review of the literature on the basis of review papers as well as research papers from reputable scientific journals, which have been published over the last few years.